Strength Studies On Slag Sand Concrete Blended With Rice Husk Ash And Glass Powder (Journal of Namibian Studies : History Politics Culture, 2023)
Concrete consists of a range of components, including coarse aggregate, fine aggregate, cement, and water. These elements are blended in various ratios to attain particular strength characteristics. However, the rapid increase in the global population and the requirement for accommodating this growth are resulting in an escalating demand for traditional construction materials. Nevertheless, the scarcity and rising costs of these materials underscore the necessity to explore alternative materials for construction. We can achieve this by incorporating various admixtures into the concrete mixture. Cement, which is a fundamental component, plays a crucial role in the concrete manufacturing process. In this paper, we present an experimental investigation focusing on the strength and workability characteristics of M30 grade concrete made with slag sand. This study involves the partial replacement of cement with rice husk ash and the addition of glass powder. Rice Husk Ash (RHA) is among the waste products generated as a by-product of rice paddy milling industries. Locally sourced glass waste was collected and processed into glass powder of suitable size. The contemporary use of glass powder as a substitute for cement aims to enhance concrete strength. The primary objective is to promote the utilization of these materials as cost-effective construction resources for low-cost buildings. In this work, cement was partially replaced with fly ash at consistent percentages of 0 ,10, 20, and 30%. Additionally, glass powder is introduced at percentages of 0, 10, and 20%. Various concrete mixtures were then produced, tested, and compared with traditional concrete. The results demonstrated an improvement in the mechanical properties with the incorporation of rice husk ash and glass powder. This project offers economic advantages, as the replacement of rice husk ash is cost-effective, and it results in the production of superior concrete.